Multimedia Health Education for Community Health Cadres: Promoting Cervical Cancer Awareness and Prevention - Endar Timiyatun; Eka Oktavianto; Woro Ispandiyah (Talenta Publisher, 2025)
Health education related to cervical cancer is essential for community empowerment, with community health cadres playing a pivotal role in delivering health education at the grassroots level. The use of appropriate educational media has been shown to effectively enhance community knowledge. This study aimed to analyze the effectiveness of educational modules and videos in improving cadres’ knowledge and skills in delivering health education on cervical cancer prevention. This quasi-experimental study employed a one-group pretest–posttest design involving 25 community health cadres. The intervention comprised two 90-minute cadre training sessions. The first session included a lecture followed by a question-and-answer discussion, while the second session involved a health education demonstration. Educational videos and modules were used as instructional media. Knowledge data were collected using a structured questionnaire, whereas skills data were assessed using a standardized observation checklist. Data were analyzed using the Wilcoxon signed-rank. The results showed that knowledge score increased from 48.00 (pretest) to 94.00 (posttest), with a mean difference of 46.00 (p < 0.05). Similarly, the mean skills score improved from 37.20 (pretest) to 87.20 (posttest), with a mean difference of 50.00 (p < 0.05). Educational modules and videos are effective media for enhancing the knowledge and skills of community health cadres in providing health education on cervical cancer prevention. Their use should be integrated into training programs to strengthen cervical cancer prevention efforts at the community level. Keyword: Cervical cancer, Health education, Cadres, Module, Video, Prevention